Description of Knowledge and Attitude of Elderly Companion After Receiving Training on Elderly Health Care - Moh Hanafi; Pramono Giri Kriswoyo; Sigit Priyanto (STIKES Ngesti Waluyo, 2022)
The elderly is one of the most at-risk group of contracting Covid-19. Due to aging process, the body will experience various declines; almost all of body organs and movement functions decrease, followed by a decrease in immunity as a body protector that does not work as strong as when it was young. Elderly companions play a role in caring for the health of the elderly, so they need knowledge and attitudes in order to have good and correct elderly health care practices. This study is a quasi-experimental study conducted with a pretest-posttest control group design with 30 respondents in the intervention group and 30 respondents in the control group. Based on the research that has been done, it shows an increase in the average value of knowledge from pre-test (28.98) to post-test (32.23) and an increase in the average value of attitude from pre-test (26.15) to post-test (29.05). Meanwhile in the second group, there was no increase in the average value of these variables. Elderly health care training is able to increase the level of knowledge and attitudes of elderly caregivers. Therefore, it is hoped that the elderly will avoid exposure to Covid-19 infection and reduce the severity of Covid-19 infection by controlling the participant's disease.